Implementasi Metode Additive Ratio Assessment (ARAS) dalam Perbandingan Mobil Blind Van di Indonesia - Setiawan, Santoso (POLITEKNIK NEGERI JAKARTA, 2024)
This research was conducted to implement the Additive Ratio Assessment (ARAS) method to evaluate and compare blind vans available in Indonesia. Blind vans are important in the context of distribution of goods and services in various economic sectors. However, with a variety of options available, the process of selecting the right one requires careful thought. The ARAS method is a multi-criteria decision evaluation tool that allows objective assessment of different criteria, such as price, reliability, fuel consumption, load capacity, and safety features. There are 4 alternatives involved for comparison, namely Daihatsu Gran Max, Suzuki New Carry, Wuling Formo, DFSK Gelora. This research will involve data collection from various sources, including information from manufacturers, customer reviews, and market data. Once the data is collected, the ARAS method will be applied to evaluate different blind vans, assign weights to relevant criteria, and generate a relative ranking for each model. The results of this study ranked the Suzuki New Carry Blind Van first with a utility degree value of 0.844 and the DFSK Gelora Blind Van last with a utility degree value of 0.628.